(untitled) (International Journal of Medical and Surgical Sciences, 2014)
The objective of this review was to present information on the main causes, possible treatments and morpho-quantitative aspects of trigeminal neuralgia. Trigeminal neuralgia is a condition characterized by intense facial pain, severe throbbing or stabbing; it is usually unilateral and recurrent and is located in the facial area innervated by the trigeminal nerve. The causes of this disease are varied and include neurovascular compression stresses. Medical treatment of choice is carbamazepine, reserving surgical treatment for cases resistant to medical therapy or cases when side effects of drugs used, outweigh the risks and disadvantages of surgery. In this context a detailed knowledge of the structure of the trigeminal nerve and its morphoquantitative characteristics could provide relevant information to make type of treatment more effective.